The impact of the digital economy on carbon emission intensity: Evidence from China - Zhao, Xiaochun; Jiang, Mei; Zhou, Ying (Frontiers in Environmental Science, 2023)
Evaluating the carbon emission reduction effect on digital economy have great significance to promote sustainable economic development and reduce carbon emissions. Based on the panel data of 30 provinces in China from 2013 to 2019, entropy- TOPSIS method and panel vector auto regressive (PVAR) model are applied in this paper to measure digital economy development level and carbon emission intensity in China then further explore the interaction between digital economy and carbon emission intensity. The results show that : First, the comprehensive development level of digital economy in China is not high, but it tends to rise slowly, from 0.208 in 2013 to 0.221 in 2019. Second, the carbon emission intensity in most provinces of China show a downward trend from 0.720 in 2013 to 0.607 in 2019,but there are significant differences in carbon emission intensity among different regions, and the overall trend is a gradual decline from west to east. Third, there is a long-term equilibrium relationship between the digital economy and the carbon emission intensity, and the two variables are Granger causality for each other. Fourth, digital economy has a long-term negative effect on carbon emission intensity, but carbon emission intensity has no negative effect on digital economy.